Cotton in Africa - (:unkn) unknown (My University, 2021)
Cotton in Africa during antiquity comes in various forms: seeds and fibers, of two different origins (Indian and African), yarns and fabrics. In addition to a circuit of cotton textiles imported from India and the South Arabian Peninsula, recent historical, archaeological, and archaeobotanical research has revealed an African culture of cotton and production of cotton fabrics, limited for the moment to the northeastern quarter of Africa. The very high added value of the product, which is also ecologically adapted to certain African environments, notably oases, has contributed to its integration into trans-Saharan and Mediterranean connectivity. This entry presents the archaeological discoveries of cotton seeds, fibers, and textiles in northeast Africa and opens avenues of reflection on a cash crop inserted in African mobility and trade relations with the Roman Mediterranean, and its potential impact on social organization.
Keywords: African Research